Experimental Research on Destruction Mode and Anchoring Performance of Carbon Fiber Phyllostachys pubescens Anchor Rod with Different Forms - Wang Yulan; Dong Zhao; Wei Lu; Lei Fan (Advances in Civil Engineering)
The anchoring technology is extensively applied in reinforcing protection of the earth relics. Now that no specification is available for different new anchor rods in earth relics protection due to diversified destruction modes of earth relics and complexity of engineering technology conditions, it is urgent to guide reinforcing design and construction with a complete detailed anchor rod research document. With the new carbon fiber Phyllostachys pubescens anchor rod as the research object, six lots of in situ tests are designed to, respectively, study the destruction mode and anchoring performance of the carbon fiber Phyllostachys pubescens anchor rod under different anchor length L, anchor rod diameter D, bore diameter H, grouting material S, rib spacing R, and inclination angle A in this paper. By studying load shift curve experiment in drawing of the anchor rod, the destruction mode and ultimate bearing capacity of the carbon fiber Phyllostachys pubescens anchor rod in different experiment lots are obtained, and the concept of permitted application value N in anchor rod design is proposed. By studying strain distribution characteristics of anchor rods in experimental lots along the length direction under action of the permitted application value N and combining the existing destruction mode and ultimate bearing capacity, this paper analyzes influences of L, D, H, S, R, and A on anchoring effect of the carbon fiber Phyllostachys pubescens anchor rod; gives the reasonable value range of L, D, H, and R when the carbon fiber Phyllostachys pubescens anchor rod is used for reinforcing design of the earth relics; and provides favorable experiment basis for reinforcing design of the earth relics based on the carbon fiber Phyllostachys pubescens anchor rod.